Cartoons on Southern Politics in National Tamil Dailies - Jeyanthan, R.; Raguram, S. (Proceedings of the 4th Jaffna University International Research Conference (JUICe2018), 2018)
Tamils predominantly live in the Northern and Eastern Provinces of the Island. Even though they depend on regional media to get the national news, they mostly rely on Tamil dailies published in Colombo for political stories. The cartoons published in national Tamil newspapers played an important contribution in expressing the political matters pertaining to the South. Hence, this study was conducted to analyze the way cartoons published in Tamil dailies reflect and captures Southern Politics through newspapers. The study was titled “Cartoons about Southern Politics on National Tamil Dailies” and explored how the Tamil newspapers; Virakesari, Thinakaran and Thinakkural present Southern Politics through cartoons. The study explored a variety of aspects such as how cartoons are capturing southern politics, the nature of symbols used in cartoons and how cartoons are reflecting critical views on political matters etc. Content analysis was employed as the research method for this study. The cartoons published by national Tamil dailies during a period of one month were collected as samples and analyzed. Interviews were conducted with cartoonists and information from these interviews was used to enrich the analysis. Even though many subjects like politics, economy and reconciliation were the themes of these cartoons, most of the cartoons were political in nature. A significant number of cartoons were drawn using symbols expressing physical attributes and with different purposes including exposing corruption, expressing the existing problems and prioritizing national interests. It is noted that political criticism was a theme used in most of the cartoons. Cartoonists have given considerable attention with the purpose of creating opinions among the public and this is being used to express the stance of the newspaper related to a subject. The study discovered that the cartoons were drawn to comment on political development and provide updated information to the public.
Keywords: National Tamil Dailies; Political Cartoons; Southern Politics; Image Representation